Ways to increase informativeness of bioelectric signals analysis - Волошин, Ю.А.; Куліш, С.Н.; Олійник, В.П. (Radiotekhnika, 2019)
Today, the limit of diagnostic capabilities of standard signal processing methods for detecting hidden changes in the physiological state of a person has been reached. In this regard, there was a need to find new approaches to the systematic analysis of biomedical signals of various physical origin. In this regard, it became necessary to search for new approaches to the system analysis of biomedical signals of various physical origin. A review of the possibilities of using various well-known methods of analyzing complex functional dependencies for processing bioelectric signals has been made. A choice of one method or another to identify the target information characteristics from an integral electrical signal of biological origin is proposed.